Osteokondros hos tjur - Wallgren, Sara (2004)
Several bulls in Sweden are culled because of lameness. Studies of beef bulls have shown that osteochondrosis is an important underlying cause of hind limb problems (Persson, 2003; Dutra, 1998). Osteochondrosis in horses, dogs, swine, poultry and man are well documentated in the literature, but there are few studies in cattle. The prevalence of osteochondrosis in dairy bulls in Sweden is unknown. The aim of this study was to investigate the presence and localisation of osteochondrosis in the hindlimbs of dairy bulls.